Bank of the United States collection - Burr, J. Kelsey
Correspondence, account books, cancelled checks, promissory notes, receipts, and other papers, relating to the first and second Bank of the United States. Correspondents include John Jacob Astor, Nicholas Biddle, Henry Clay, William H. Crawford, J.J. Crittenden, Albert Gallatin, Richard Henry Lee, Isaac Melcher, James Monroe, Joseph Nourse, Richard Rush, John Sergeant, and Daniel Webster.
Collector.
Collection material in English.
Keywords: Astor, John Jacob, -- 1763-1848 -- Correspondence; Biddle, Nicholas, -- 1786-1844 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Crawford, William Harris, -- 1772-1834 -- Correspondence; Crittenden, John J. -- 1787-1863 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Lee, Richard Henry, -- 1732-1794 -- Correspondence; Melcher, Isaac -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Nourse, Joseph, -- 1754-1841 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Sergeant, John, -- 1779-1852 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Bank of the United States (1791-1811); Bank of the United States (1816-1836); Banks and banking -- United States; Collectors